Hematological and biochemical profile of captive brown-throated sloths Bradypus variegatus, Schinz 1825, feeding on ambay pumpwood Cecropia pachystachya Trécul 1847 - M.C. Tschá; G.P. Andrade; P.V. Albuquerque; A.R. Tschá; G.S. Dimech; C.J.F.L. Silva; E.T.N. Farias; M.J.A.A.L. Amorim (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2021)
ABSTRACT The aim of this study was to establish reference parameters for the hematological and biochemical levels of five healthy captive sloths of the speciesBradypus variegatus(brown-throated sloth) feeding onCecropia pachystachya(Ambay pumpwood), alternating with a period of free diet in the Dois Irmãos State Park (DISP) Recife, Pernambuco - Brazil.